Metabolic modeling of denitrification in Agrobacterium tumefaciens: a tool to study inhibiting and activating compounds for the denitrification pathway - Kampschreur, Marlies J.; Kleerebezem, Robbert; Picioreanu, Cristian; Bakken, Lars R.; Bergaust, Linda; de Vries, Simon; Jetten, Mike S.; Van Loosdrecht, Mark C. (Frontiers in Microbiology, 2012)
A metabolic network model for facultative denitrification was developed based on experimental data obtained with Agrobacterium tumefaciens. The model includes kinetic regulation at the enzyme level and transcription regulation at the enzyme synthesis level. The objective of this work was to study the key factors regulating the metabolic response of the denitrification pathway to transition from oxic to anoxic respiration and to find parameter values for the biological processes that were modelled. The metabolic model was used to test hypotheses that were formulated based on the experimental results and offers a structured look on the processes that occur in the cell during transition in respiration. The main phenomena that were modelled are the inhibition of the cytochrome c oxidase by nitric oxide (NO), the (indirect) inhibition of oxygen on the denitrification enzymes. The activation of transcription of nitrite reductase and NO reductase by their respective substrates were hypothesized. The general assumption that nitrite and NO reduction are controlled interdependently to prevent NO accumulation does not hold for A. tumefaciens. The metabolic network model was demonstrated to be a useful tool for unravelling the different factors involved in the complex response of A. tumefaciens to highly dynamic environmental conditions.